Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To determine the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy the given system of equations:
[tex]\[ \left\{\begin{array}{l} 3x + 2y = 14 \\ x = 4y - 2 \end{array}\right. \][/tex]
we will proceed step-by-step:
1. Substitute the second equation into the first equation:
The second equation gives [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ x = 4y - 2 \][/tex]
Substitute [tex]\( x = 4y - 2 \)[/tex] into the first equation:
[tex]\[ 3(4y - 2) + 2y = 14 \][/tex]
2. Simplify and solve for [tex]\( y \)[/tex]:
Expand and combine like terms:
[tex]\[ 12y - 6 + 2y = 14 \][/tex]
Combine the [tex]\( y \)[/tex] terms:
[tex]\[ 14y - 6 = 14 \][/tex]
Add 6 to both sides:
[tex]\[ 14y = 20 \][/tex]
Divide by 14:
[tex]\[ y = \frac{20}{14} = \frac{10}{7} \][/tex]
3. Substitute [tex]\( y = \frac{10}{7} \)[/tex] back into the second equation to solve for [tex]\( x \)[/tex]:
Using [tex]\( x = 4y - 2 \)[/tex]:
[tex]\[ x = 4\left(\frac{10}{7}\right) - 2 \][/tex]
[tex]\[ x = \frac{40}{7} - 2 \][/tex]
[tex]\[ x = \frac{40}{7} - \frac{14}{7} \][/tex]
[tex]\[ x = \frac{26}{7} \][/tex]
Thus, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy the system of equations are:
[tex]\[ \left(\frac{26}{7}, \frac{10}{7}\right) \][/tex]
Therefore, the correct answer is:
[tex]\(\left(\frac{26}{7}, \frac{10}{7}\right)\)[/tex]
[tex]\[ \left\{\begin{array}{l} 3x + 2y = 14 \\ x = 4y - 2 \end{array}\right. \][/tex]
we will proceed step-by-step:
1. Substitute the second equation into the first equation:
The second equation gives [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ x = 4y - 2 \][/tex]
Substitute [tex]\( x = 4y - 2 \)[/tex] into the first equation:
[tex]\[ 3(4y - 2) + 2y = 14 \][/tex]
2. Simplify and solve for [tex]\( y \)[/tex]:
Expand and combine like terms:
[tex]\[ 12y - 6 + 2y = 14 \][/tex]
Combine the [tex]\( y \)[/tex] terms:
[tex]\[ 14y - 6 = 14 \][/tex]
Add 6 to both sides:
[tex]\[ 14y = 20 \][/tex]
Divide by 14:
[tex]\[ y = \frac{20}{14} = \frac{10}{7} \][/tex]
3. Substitute [tex]\( y = \frac{10}{7} \)[/tex] back into the second equation to solve for [tex]\( x \)[/tex]:
Using [tex]\( x = 4y - 2 \)[/tex]:
[tex]\[ x = 4\left(\frac{10}{7}\right) - 2 \][/tex]
[tex]\[ x = \frac{40}{7} - 2 \][/tex]
[tex]\[ x = \frac{40}{7} - \frac{14}{7} \][/tex]
[tex]\[ x = \frac{26}{7} \][/tex]
Thus, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy the system of equations are:
[tex]\[ \left(\frac{26}{7}, \frac{10}{7}\right) \][/tex]
Therefore, the correct answer is:
[tex]\(\left(\frac{26}{7}, \frac{10}{7}\right)\)[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.